2007
DOI: 10.1074/jbc.m701214200
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2-EP4 Receptor Promotes Endothelial Cell Migration via ERK Activation and Angiogenesis in Vivo

Abstract: Prostaglandin E2 (PGE 2 ), a major product of cyclooxygenase, exerts its functions by binding to four G protein-coupled receptors (EP1-4) and has been implicated in modulating angiogenesis. The present study examined the role of the EP4 receptor in regulating endothelial cell proliferation, migration, and tubulogenesis. Primary pulmonary microvascular endothelial cells were isolated from EP4 flox/flox mice and were rendered null for the EP4 receptor with adenoCre virus. Whereas treatment with PGE 2 or the EP4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 39 publications
(19 reference statements)
7
101
0
1
Order By: Relevance
“…In vivo blockade of COX-2/ PGE 2 with SC58125 not only decreased MDSC and Treg accumulation in 3LL/Fas-WT tumor tissues, but also reduced the tumor growth and prolonged the survival of 3LL/Fas-WT-bearing mice, thus further indicating that PGE 2 plays an important role in the promotion of 3LL lung cancer growth by Fas signal. PGE 2 receptors EP2 and EP4 are involved in the PGE 2 -mediated DC migration (30,31). We confirmed that both EP2 and EP4 were expressed in MDSC by RT-PCR, also EP2/EP4 were expressed in 3LL cells.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In vivo blockade of COX-2/ PGE 2 with SC58125 not only decreased MDSC and Treg accumulation in 3LL/Fas-WT tumor tissues, but also reduced the tumor growth and prolonged the survival of 3LL/Fas-WT-bearing mice, thus further indicating that PGE 2 plays an important role in the promotion of 3LL lung cancer growth by Fas signal. PGE 2 receptors EP2 and EP4 are involved in the PGE 2 -mediated DC migration (30,31). We confirmed that both EP2 and EP4 were expressed in MDSC by RT-PCR, also EP2/EP4 were expressed in 3LL cells.…”
Section: Discussionsupporting
confidence: 68%
“…As PGE 2 can promote migration of cells including DC (29,30) and endothelial cells (31). Then we tested whether the increased production of PGE 2 by Fas-ligated cancer cells was responsible for the increased chemoattraction of MDSC.…”
Section: Pge 2 Derived From the Fas-ligated Lung Cancer Cells Contribmentioning
confidence: 99%
“…Furthermore, endothelial cells regulate PCDH12 shedding in response to cytokines known to induce the cAMP or the PKC pathways. Endothelial cells mainly express PGE 2 receptors EP2 and EP4, two G protein-coupled receptors that both stimulate adenylate cyclase via stimulatory subunit Gs, whereas VEGF activates the phospholipase C-PKC pathway through VEGFR2 (33,34). As expected, VEGF enhanced PCDH12 shedding, whereas PGE 2 inhibited basal as well as VEGF-induced cleavage.…”
Section: Discussionmentioning
confidence: 79%
“…HUVECs were challenged either with VEGF that activates PKC, with PGE 2 that stimulates cAMP synthesis, or with histamine, which activates both pathways through H1 and H2 receptors, respectively (33,34). Both VEGF and histamine significantly increased PCDH12 shedding, and PGE 2 diminished basal PCDH12 shedding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Предыдущие исследования по-казывают, что глюкокортикоиды подавляют ангиогенез путем ингибирования синтеза VEGF [18,19,20], что до-казывает ингибирующее действие кортизола на сиг-нальные пути, который инициирует образование тубул.…”
Section: кортизол и кардиоваскулярные рискиunclassified